Local development in fragile areas - Francesca Governa (Revue de Géographie Alpine)
During the last 20 years some keywords have been extensively used in international debate about local development policies: bottom-up approach, territoriality, policy integration, partnership, cooperation and negotiation among actors and interests. The use of these keywords hides a variety of cultural approaches, theories and practices; this means that we should study local development processes and policies analysing and deconstructing these theoretical approaches in specific situations and experiences. Within this framework, the article critically discuss local development policies involving “fragile” areas like those of the mountains in Lombardy. Reference will be made mainly to the results of a research-action activity on the integrated local development programmes (PISL) for the Objective 2 areas of the Region financed during the period of European structural funds programming 2000-2006.